Intervenções com pais: Da alteração das práticas educativas parentais à inclusão de variáveis de contexto - Silveira, Fabiane Ferraz [UNESP] (Tikinet Edicao, 2011)
This paper aims to discuss aspects of some parent skills training program giving greater emphasis to families who concomitantly are faced with behavior problems and marital conflicts. From this view, discusses in the following section a retrospect, as the parent training program progressed until the present time; contextual variables and its relations with behavior problems and results of interventions; studies that include as objectives the reduction of behavior problems associated with the modification of conjugal relationship. In the end, the paper points out limitations and advances for further studies.
Interventions with parents: The modification of parental practices and the inclusion of contextual variables
Keywords: Behavior problems; Contextual variables; Parental practices